The prognostic value of health-related quality of life for early molecular response in patients with chronic myeloid leukemia: analysis of the GIMEMA-SUSTRENIM trial - Efficace, Fabio; Cannella, Laura; Capodanno, Isabella; Sancetta, Rosaria; Porcu, Veronica; Lunghi, Monia; Biagi, Annalisa; Castagnetti, Fausto; Caocci, Giovanni; Baldi, Thomas; Marasca, Roberto; Bonifacio, Massimiliano; et al. (Frontiers in Oncology, 2025)
We aimed to explore the prognostic value of patient-reported health-related quality of life (HRQoL) data for the achievement of early molecular response (EMR) at 3 months in patients with chronic phase chronic myeloid leukemia (CP-CML). We analyzed HRQoL baseline data of 436 newly diagnosed patients with CML patients enrolled in the GIMEMA Sustrenim trial. HRQoL was assessed by the EORTC QLQ-30 and the QLQ-CML24 questionnaires. In the multivariate analysis, the following factors were found to be independently associated with achievement of EMR: Sokal risk (low vs intermediate risk p=0.046 and low vs high risk p<0.001), nilotinib treatment (p<0.001) and higher patient-reported role functioning (EORTC QLQ-C30) (p<0.001). Current findings suggest the importance of assessing HRQoL at diagnostic workup of patients with CML as it may provide valuable prognostic information.